Phenotypic and Transcriptomic Analyses Reveal the Cell Membrane Damage of Pseudomonas fragi Induced by Cinnamic Acid - Zhang, Yuxiang; Wei, Jianping; Guo, Hong; Niu, Chen; Yuan, Yahong; Yue, Tianli (Frontiers in Microbiology, 2022)
Cinnamic acid (CA) is a safe and effective antimicrobial agent. The objective of this study was to reveal the antibacterial mechanism of CA against a food-derived Pseudomonas fragi 38-8, from the aspects of bacterial growth kinetics, cell membrane homeostasis, cell microstructure, and transcription. The minimum inhibitory concentration (MIC) of CA against P. fragi 38-8 was 0.25 mg/mL. CA retarded bacterial growth, and induced a series of cell membrane changes. After CA treatment, cell membrane homeostasis was destroyed, which was evidenced by cell membrane depolarization, intracellular pH reduction, and intracellular ATPase activity decrease. Field emission scanning electron microscope (FESEM), transmission electron microscope (TEM) and confocal laser scanning fluorescence microscope (CLSM) realized the visualization of cell microstructure changes, showing cell death and morphological changes such as cell rupture, shrinkage, and hollowness. RNA sequencing analysis further confirmed the effects of CA to the cell membrane, because of the significant enrichment of differentially expressed genes (DEGs) related to membrane. The results of the phenotype tests and RNA-Seq both focused on cell membrane damage, which showed that CA exerted antibacterial effect mainly by acting on cell membrane.